An mRNA-Based Multiple Antigenic Gene Expression System Delivered by Engineered Salmonella for Severe Fever with Thrombocytopenia Syndrome and Assessment of Its Immunogenicity and Protection Using a Human DC-SIGN-Transduced Mouse Model - Ji-Young Park; Chamith Hewawaduge; Chandran Sivasankar; Khristine Kaith S. Lloren; Byungkwan Oh; Mi Young So; John Hwa Lee (MDPI AG, 2023)
Currently, there are no commercial vaccines or therapeutics against severe fever with thrombocytopenia syndrome (SFTS) virus. This study explored an engineered Salmonella as a vaccine carrier to deliver a eukaryotic self-mRNA replicating vector, pJHL204. This vector expresses multiple SFTS virus antigenic genes for the nucleocapsid protein (NP), glycoprotein precursor (Gn/Gc), and nonstructural protein (NS) to induce host immune responses. The engineered constructs were designed and validated through 3D structure modeling. Western blot and qRT-PCR analyses of transformed HEK293T cells confirmed the delivery and expression of the vaccine antigens. Significantly, mice immunized with these constructs demonstrated a cell-mediated and humoral response as balanced Th1/Th2 immunity. The JOL2424 and JOL2425 delivering NP and Gn/Gc generated strong immunoglobulin IgG and IgM antibodies and high neutralizing titers. To further examine the immunogenicity and protection, we utilized a human DC-SIGN receptor transduced mouse model for SFTS virus infection by an adeno-associated viral vector system. Among the SFTSV antigen constructs, the construct with full-length NP and Gn/Gc and the construct with NP and selected Gn/Gc epitopes induced robust cellular and humoral immune responses. These were followed by adequate protection based on viral titer reduction and reduced histopathological lesions in the spleen and liver. In conclusion, these data indicate that recombinant attenuated Salmonella JOL2424 and JOL2425 delivering NP and Gn/Gc antigens of SFTSV are promising vaccine candidates that induce strong humoral and cellular immune responses and protection against SFTSV. Moreover, the data proved that the hDC-SIGN transduced mice as a worthy tool for immunogenicity study for SFTSV.